Prognostic significance of venous invasion in node‐negative head and neck squamous cell carcinoma. (1st December 2019) - Gopinath, Arun; Mubeen, Aysha; Baskovich, Brett; Mohammed, Ibraheem; Makary, Raafat; Hoy, Erica S.; Dagan, Roi; Smotherman, Carmen; Gautam, Shiva; Fernandes, Rui P.; Bunnell, Anthony M.; Pirgousis, Phillip; et al.
Abstract: Background: Venous invasion (VI) is not frequently evaluated on routine histologic examination of head and neck squamous cell carcinoma (HNSCC), and the prognostic significance is largely unknown. Studies have shown that extramural venous invasion is an adverse prognostic factor in colorectal carcinoma. To our knowledge, this is the first study evaluating the prognostic significance of venous invasion in node‐negative (without clinical or pathologic evidence of lymph node involvement) HNSCC, utilizing the elastic stain. Methods: A total of 105 consecutive lymph node‐negative (N0) HNSCC were evaluated for the presence of venous channel invasion by tumor utilizing the elastin stain. Clinical, demographic, and follow‐up data were recorded. Results: Of 37 patients with venous invasion, 19% had loco‐regional recurrence, as opposed to 12% of those without. Univariate analysis revealed statistically significant decreased recurrence‐free survival in the presence of venous invasion (log‐rank [Mantel‐Cox] test P ‐value .025). Conclusion: Identification of VI is greatly aided by elastic stain. In patients with node‐negative HNSCC, presence of VI resulted in decreased recurrence‐free survival on univariate analysis. The impact of VI as a prognostic marker should be further evaluated.